2019
DOI: 10.1530/erc-18-0354
|View full text |Cite
|
Sign up to set email alerts
|

Neuroendocrine neoplasms: current and potential diagnostic, predictive and prognostic markers

Abstract: Some biomarkers for functioning and non-functioning neuroendocrine neoplasms (NENs) are currently available. Despite their application in clinical practice, results should be interpreted cautiously. Considering the variable sensitivity and specificity of these parameters, there is an unmet need for novel biomarkers to improve diagnosis and predict patient outcome. Nowadays, several new biomarkers are being evaluated and may become future tools for the management of NENs. These biomarkers include (1) peptides a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
38
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(41 citation statements)
references
References 218 publications
(200 reference statements)
0
38
0
1
Order By: Relevance
“…A significant challenge for the use of ctDNA in the NEN field is the relative lack of recurrent mutations in comparison with other tumors. Requirements for accurate ctDNA analysis include adequate tumor DNA being shed into the blood stream and a PCR primer based assay that detects the mutations of interest [34]. Unfortunately, these conditions are only present in a small subset of NET patients population [34].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A significant challenge for the use of ctDNA in the NEN field is the relative lack of recurrent mutations in comparison with other tumors. Requirements for accurate ctDNA analysis include adequate tumor DNA being shed into the blood stream and a PCR primer based assay that detects the mutations of interest [34]. Unfortunately, these conditions are only present in a small subset of NET patients population [34].…”
Section: Discussionmentioning
confidence: 99%
“…Requirements for accurate ctDNA analysis include adequate tumor DNA being shed into the blood stream and a PCR primer based assay that detects the mutations of interest [34]. Unfortunately, these conditions are only present in a small subset of NET patients population [34]. In small bowel NET, tissue-based genomic sequencing revealed that the majority of recurrent mutations were in cyclin-dependent kinase inhibitor CDKN1B (8% of cases) [35].…”
Section: Discussionmentioning
confidence: 99%
“…While most (potential) prognostic NEN biomarkers are applicable to a subset of NENs, e.g. pancreatic or lung NENs, reduced PAM staining www.nature.com/scientificreports/ demonstrated utility across a spectrum of NENs 35 . Particularly notable findings of this study were: (A) PAM scoring was highly consistent among three independent reviews; (B) reduced PAM staining was associated with a stage-independent increased risk of death and shorter survival duration among patients who died; and (C) reduced PAM immunoreactivity may identify grade 1 or grade 2 NENs in patients with an increased risk of dying.…”
Section: Discussionmentioning
confidence: 99%
“…However, there is a lack of alternatives beyond the use of fasting gut hormones. Alternative possible biomarkers in the form of growth factors, such as VEGF and its receptors, placental growth factor (PlGF), Interleukin-8 (IL-8), PD-1/PD-L1 expression, T-cell immunoglobulin and mucin domain 3 (TIM3), X-linked transcriptional regulator (ATRX), death domain-associated protein 6 (DAXX) genes, circulating tumour cells, and circulating tumour DNA, have been studied without consensus on their utility [148][149][150][151][152]. The use of biomarkers can be employed beyond the selection of patients for specific therapies; understanding the biology of PanNETs, especially the mechanisms of acquired resistance (for example, to targeted therapy, although this applies equally to other treatments) is needed.…”
Section: Ongoing Challengesmentioning
confidence: 99%